2015
DOI: 10.1534/g3.114.016485
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Markers for Western Corn Rootworm Resistance to Bt Toxin

Abstract: Western corn rootworm (WCR) is a major maize (Zea mays L.) pest leading to annual economic losses of more than 1 billion dollars in the United States. Transgenic maize expressing insecticidal toxins derived from the bacterium Bacillus thuringiensis (Bt) are widely used for the management of WCR. However, cultivation of Bt-expressing maize places intense selection pressure on pest populations to evolve resistance. Instances of resistance to Bt toxins have been reported in WCR. Developing genetic markers for res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 32 publications
6
56
0
Order By: Relevance
“…Similar to previous results with Lepidoptera [34], fragments of this cadherin synergize Cry3Aa and Cry3Bb activity against Diabrotica and Leptinotarsa [35] and the lesser mealworm, Alphitobius diaperinus [36], and a similar result was found for the cadherin from the mealworm, Tenebrio molitor [20]. The demonstration of genetic linkage between an ABC protein and Cry3Bb1 resistance in D. virgifera [16] was the first confirmation from Coleoptera of similar results in Lepidoptera [12,37]. In addition to a linkage analysis, our results add the molecular identity of the mutation in C. tremula , and a demonstration of the role of the CtABCB1 protein in cell killing by the Cry3Aa toxin.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to previous results with Lepidoptera [34], fragments of this cadherin synergize Cry3Aa and Cry3Bb activity against Diabrotica and Leptinotarsa [35] and the lesser mealworm, Alphitobius diaperinus [36], and a similar result was found for the cadherin from the mealworm, Tenebrio molitor [20]. The demonstration of genetic linkage between an ABC protein and Cry3Bb1 resistance in D. virgifera [16] was the first confirmation from Coleoptera of similar results in Lepidoptera [12,37]. In addition to a linkage analysis, our results add the molecular identity of the mutation in C. tremula , and a demonstration of the role of the CtABCB1 protein in cell killing by the Cry3Aa toxin.…”
Section: Discussionsupporting
confidence: 87%
“…These showed a four-base-pair deletion at position 1561 (GenBank Accession KX686490, Figure S1), introducing a frame shift with a premature stop codon leading to loss of the TpM1 transporter motif as well as the complete second transmembrane domain (Figure 1). A homolog of CtABCB1 in the western corn rootworm, Diabrotica virgifera virgifera , was shown to be genetically linked to resistance to the Bt Cry3Bb1 toxin; however, the resistance-conferring mutation was not reported [16] (Figure S4). The existence of cross-resistance between Cry3Bb1 and mCry3A (a modified version of Cry3Aa) in the western corn rootworm [17] suggested that CtABCB1 could be involved in resistance to Cry3Aa in C. tremula , and we investigated it further.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Flagel et al. (, ) found that genetic markers within a QTL for resistance in the Hopkinton strain did not distinguish between other susceptible and resistant field populations of WCR.…”
Section: Discussionmentioning
confidence: 98%
“…Mutations in the ABC transporter sequences in H. virescens and B. mori decreased binding of Cry toxins (Atsumi et al., ; Gahan et al., ) and ABCC2 was found to be one of the genes present in a mapping study of the locus for resistance to Cry1Ac in P. xylostella and T. ni (Baxter et al., ) and in Cry1Fa‐resistant O. nubilalis (Coates & Siegfried, ). A mapping study in WCR also identified a link between Cry3Bb1 resistance and a gene coding for ABCB2 (Flagel et al., ) , an ABC transporter of a different family than the families of ABC transporters identified in Lepidoptera. Moreover, an ABCB2 has been genetically linked to Cry3A resistance and to its mode of action in another Chrysomelid, Chysomela tremula Fabricius (Pauchet et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the recently observed resistance of some Lepidoptera and beetle pests has reduced these benefits (9) and is becoming the most serious threat to the continued efficacy of Bt crops. The "pyramided" strategy has been widely used to significantly delay resistance (10,11).…”
mentioning
confidence: 99%